2003
DOI: 10.1046/j.1365-2249.2003.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

High serum vascular endothelial growth factor correlates with disease activity of spondylarthropathies

Abstract: SUMMARY Angiogenesis is involved in chronic inflammatory joint diseases such as rheumatoid arthritis (RA). Vascular endothelial growth factor (VEGF) plays a crucial role in angiogenesis. The spondylarthropathies (SpA) are characterized by enthesitis and synovitis, in which blood vessels participate. The objective of this study was to investigate serum VEGF levels and their potential associations with disease activity markers for SpA. Sera were collected from 105 patients with SpA (72 with ankylosing spondyliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
58
2
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 18 publications
6
58
2
5
Order By: Relevance
“…2,3,6 Previous studies demonstrated a positive correlation between serum VEGF levels and disease activity indices such as BASDAI, ESR, and CRP in patients with spondyloarthritis. 3,4,6 Likewise, other investigators have demonstrated positive correlations between serum VEGF and CRP and BASDAI in AS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6 Previous studies demonstrated a positive correlation between serum VEGF levels and disease activity indices such as BASDAI, ESR, and CRP in patients with spondyloarthritis. 3,4,6 Likewise, other investigators have demonstrated positive correlations between serum VEGF and CRP and BASDAI in AS.…”
Section: Resultsmentioning
confidence: 99%
“…1 The role of angiogenesis has not been clearly established in patients with AS. [2][3][4][5][6] Cytokines involved in angiogenesis include, among others, vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), basic fibroblast growth factor (bFGF), and acidic fibroblast growth factor (aFGF). 7 The source of VEGF in serum is unclear; it may be derived from platelets, inflamed synovial tissue, or other sources.…”
mentioning
confidence: 99%
“…Increased serum level of VEGF was demonstrated in patients with AS (8) and correlated with the activity of the disease (BASDAI, C-reactive protein) (9). A predictive effect of the serum level of VEGF on radiographic progression was also recently demonstrated (10).…”
mentioning
confidence: 95%
“…Не исключено, что нарушение кровоснабжения в указанных областях, тканевые иммуно-воспалительные реакции и неоангиогенез взаимообуслов-лены. Однако сведения о взаимосвязи между повышением уровня перечисленных цитокинов в крови и клинико-ла-бораторными параметрами воспаления при ПсА, а также реологическими свойствами крови весьма ограничены [9,10]. С нашей точки зрения, полученные данные помогут понять некоторые аспекты патогенеза ПсА, в том числе и с позиции участия воспаления в формировании кардиова-скулярного риска (КВР) при данном заболевании.…”
unclassified
“…У 105 больных с заболевания-ми из группы спондилоартритов (преимущественно с анкилозирующим спондилитом) найдена прямая корреляция между повышением уров-ня СЭФР в сыворотке крови и индексом активности BASDAI, а также CРБ и СОЭ [20].…”
unclassified